Estrogen, menopause, and Alzheimer’s disease: understanding the link to cognitive decline in women - Mervosh, Nicholas; Devi, Gayatri (Frontiers in Molecular Biosciences, 2025)
BackgroundWomen face a significantly higher lifetime risk of developing Alzheimer’s disease (AD) than men. This disparity is often attributed to longer female longevity, but growing evidence suggests a multifactorial origin, including hormonal, vascular, and immunologic contributions. Estrogen plays a critical neuroprotective role across multiple systems implicated in AD pathogenesis, including synaptic plasticity, mitochondrial function, and cerebrovascular integrity. However, clinical trials investigating hormone therapy (HT) for AD prevention have yielded mixed results, in part due to variability in study populations, timing of intervention, and formulation of hormones.Aims/methodsThis review examines the biological rationale for estrogen’s role in cognitive aging, synthesizes clinical and translational data on hormone therapy and AD risk, and highlights the importance of vascular comorbidity, including cerebral small vessel disease, in mediating AD pathology.ConclusionWe propose that estrogen’s neuroprotective potential may be best realized in personalized treatment frameworks that account for age, timing, APOE genotype, and vascular burden. Interpretation of estrogen’s role in AD is further complicated by variability in diagnostic criteria, which may contribute to conflicting findings across studies. Recognition of menopause-related cognitive impairment as an early, hormonally modulated risk state may offer additional opportunity for timely intervention. Addressing this complexity is essential to refining AD prevention strategies in midlife women.